Methods and models of development of innovative technologies in large enterprises marketing - Ахмедов, Ренат Рамазанович (Technology audit and production reserves, 2015)
It is studied software marketing activities for solving marketing problems. Automation of marketing activities in the enterprise has a number of significant advantages, such as faster and more efficient creation and promotion of content, advanced management of marketing companies, the ability to monitor the activity of visitors to the site. This article examines contemporary issues in the field of marketing research. There was also defined relationship with the degree of marketing innovations to various factors, among which the most weight is the geographical position of the country and the overall economic development. This study is aimed at the selection of functions to the needs of specific objects of automation and analysis of the programs used in the marketing activities of large enterprises. As a result of the study were presented groups, systems, marketing automation. Software, used in the marketing activities, has the different features and is selected in accordance with the specifics and requirements of a particular enterprise. In this article it is analyzed such systems as Integrated Marketing Management, MRM-system and EFM-system, derived their main features, advantages and disadvantages. This work is also an analysis of the program automation of marketing and marketing research, it examines the prospects for the development of innovations in the marketing of large enterprises.